MULTI PERIOD SHOCKS ROLES ON GOVERNMENT SPENDING IN INDONESIA - Jaka Sriyana (Economic Journal of Emerging Markets, 2010)
This paper proposes an alternative dynamic model of government spending in Indonesia. The model is based on short term disequilibrium assumption, in which multi period of shocks variables may play an important role. This research applies a loss function approach and uses optimum shock variables as the determinant for government spending during 1970-2010. The result shows that real GDP, population, and multi period shock of government spending are statistically significant. It provides evidence of the impact of multi period shocks to the realization of government spending. It implies that government faces a serious disequilibrium in determining their spending both in short and long terms.Keywords: Fiscal, government spending, deficit budget, shockJEL classification numbers: H53, H62, C22